Implementasi Konvensi Internasional Tentang Perlindungan Hak Pekerja Asing dan Anggota Keluarganya: Studi Kasus Penjaminan Hak Pekerja Migran Indonesia Di Singapura - Rizki, Khairur (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
The International Convention on the Protection of the rights of foreign workers and their family members is a convention imposed on 1 June 2003. The convention was formed in order to protect migrant workers in a country. This Convention gives Justice the same rights to migrant workers and local workers in a country. Such rights may be the right to travel, the right to change of employment, the right to gather with the family, the right to organize, and the right to acknowledgment of the documents or not documents. This Paper aims to determine the success or presence of countries that ratify this Convention. and case studies on this paper using the country of Indonesia. From the data we can and we collect, it can be concluded that the country of Indonesia ratified this Convention but failed to apply this Convention to its country due to migrant workers who are treated unreasonably in the country where it works.